Spatial and temporal pattern of expression of the wingless and engrailed genes in the adult antenna is regulated by age-dependent mechanisms. - Rogina, B.; Helfand, S.L. (Mechanisms of Development, 1997)
The spatial and temporal pattern of expression of enhancer trap lines reporting on the wingless (wg) and engrailed (en) genes was characterized in the adult antenna of Drosophila melanogaster. The time courses of expression seen for wg and en, although different from each other, reveal a complex well-controlled pattern of temporal expression, providing evidence that regulatory mechanisms are preserved throughout the life span of the adult fly. Altering the life span demonstrates that the temporal patterns of expression of both wg and en are linked to life span. These studies suggest that the expression of wg and en in the adult antenna is controlled by age-dependent mechanisms.